Concomitant Bandage Contact Lens, Oral Nicergoline, and Topical Autologous Serum for Severe Neurotrophic Keratitis. Issue 3 (7th March 2023) - Polania-Baron, Eduardo J.; Graue-Hernandez, Enrique O.; Ramirez-Miranda, Arturo; Navas, Alejandro
Abstract : Background: To report the outcomes of using the combination of oral nicergoline, autologous serum, and contact lens to enhance corneal epithelization in neurotrophic keratitis and to discuss the clinical potential of this management. Methods: This was a prospective consecutive case series study of eight patients treated for neurotrophic keratitis at the "Conde de Valenciana" Institute of Ophthalmology. Oral nicergoline, autologous serum, and bandage contact lens were initiated at the same time, immediately after stage 3 diagnosis keratitis was confirmed clinically, and until corneal epithelialization was achieved or eminent corneal perforation was seen. In patients where diabetes was a cause, glycosylate hemoglobin was measured to asses metabolic control. Corneal esthesiometry and corrected distance visual acuity were assessed before and after treatment. Results: This study included eight eyes of eight patients (5 men [62.5%], average age 57±17.9 years). All patients completed at least 1 month of follow-up after nicergoline and contact lens suspension. Of the eight eyes, no one had positive culture growth and complete epithelial healing was achieved in all cases. Half of patients had diabetes and had a poor metabolic control. Corneal sensitivity improved in all eyes almost 2 centimeters in Cochet–Bonnet esthesiometry ( P= 0.01). In addition, final visual acuity gains were obtained ( P= 0.100). Conclusions: The combination of oral nicergoline, autologous serum, and bandage contact lens simultaneously could be an alternative in the management of stage 3 neurotrophic keratitis when conventional medical treatment has no improvement of corneal epithelization.